2020
DOI: 10.1002/nop2.451
|View full text |Cite
|
Sign up to set email alerts
|

Practices of pica among pregnant women in a tertiary healthcare facility in Ghana

Abstract: Aim This study assessed the practice of pica among pregnant women in the Ho Teaching Hospital. Design Descriptive cross‐sectional. Methods Systematic sampling technique was used to recruit 286 pregnant women. Questionnaire was used to collect data. Data entered into Statistical Package for Social Sciences for analysis. Result Of the 286 pregnant women, 21.2% and 17.8% considered white clay and ice respectively as nutritious. Prevalence of pica was 47.5%, while 44.9% of pregnant women who practised pica reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
1
12
2
Order By: Relevance
“…Food aversion prevalence (45%) was comparable to findings which were also conducted in Ghana (44.8%) by [ 55 ] and in Kenya [ 58 ] but lower than those reported by [ 19 ] and [ 59 ] in Tanzania and Ecuador respectively. Current findings show the practice of pica during pregnancy (39%) was slightly lower than studies conducted in Ghana by [ 42 , 55 , 60 ] which were between 47–48% but higher than those conducted in Kenya [ 58 ] and Ethiopia [ 61 ] which were 27% and 30% respectively. Regression analysis showed that participants who practiced food craving had higher odds for inadequate DD.…”
Section: Discussioncontrasting
confidence: 64%
“…Food aversion prevalence (45%) was comparable to findings which were also conducted in Ghana (44.8%) by [ 55 ] and in Kenya [ 58 ] but lower than those reported by [ 19 ] and [ 59 ] in Tanzania and Ecuador respectively. Current findings show the practice of pica during pregnancy (39%) was slightly lower than studies conducted in Ghana by [ 42 , 55 , 60 ] which were between 47–48% but higher than those conducted in Kenya [ 58 ] and Ethiopia [ 61 ] which were 27% and 30% respectively. Regression analysis showed that participants who practiced food craving had higher odds for inadequate DD.…”
Section: Discussioncontrasting
confidence: 64%
“…Food aversion prevalence (45%) was comparable to findings which were also conducted in Ghana (44.8%) by (52) and in Kenya (49%) by (57) but lower than those reported by (18) and (56) in Tanzania (70%) and Ecuador (74%) respectively. Current findings show practice of pica during pregnancy (39%) was slightly lower than studies conducted in Ghana by (46,52,58) which were between 47 – 48% but higher than those conducted in Kenya (57) and Ethiopia (59) which were 27% and 30% respectively. Regression analysis showed that participants who did not practice pica and food aversion had higher odds for adequate DD.…”
Section: Discussioncontrasting
confidence: 64%
“…Similarly, (Salih et al, 2015) study which done in Jizan and showed 67.3%. In the same line, two studies conducted in Ghana (Konlan et al, 2020) and (Hommey, 2016) reported that pica was more than three-quarters among participants of pregnant women. Moreover, studies conducted in Tanzania by (Nyanza et al, 2014) and in Nigeria by (Ekwenchi et al, 2015) which reported that about half of pregnant 53% of women have the urge to eat non-food items or pica.…”
Section: Discussionmentioning
confidence: 83%
“…These alternatives may include eating dry bread, biscuits, or sweets to reduce the effects of pregnancy nausea and vomiting. Health workers should increase health education on pica and its adverse impact on mothers and fetus health (Doyle & Spallek, 2016;Konlan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%